Transformasi Digital Manajemen Keuangan Umkm Melalui Workshop Penerapan Aplikasi Labamu Dan Pencatatan Keuangan Yang Efisien - Wahyudiono, Andhika (PT Ininnawa Paramacitra Edu, 2024)
Financial management of MSMEs in Kacangan Asri is difficult. Lack of understanding of financial management results in ineffective cash flow and debt planning. The lack of digital skills hinders technology adoption, making MSMEs hesitant to use digital systems. Difficulties in financial risk management trigger unmanageable debt. Objectives This service activity aims to provide a comprehensive understanding of financial management to MSME actors. Training is conducted using digital and manual approaches to improve their financial literacy. The method of implementing activities begins with coordination between related parties. Coordination ensures an understanding of the role and support of each in the workshop programme. The implementation of the workshop uses lecture and practice methods, where financial materials and guidelines for using the Labamu application. Results and discussion: Community service activities that focus on increasing financial literacy and technology adoption among MSME actors have a positive impact on increasing their understanding of financial management. The workshop, which was carried out using lecture and hands-on methods, helped participants understand the importance of recording cash flow, debt management, and effective financial planning. Through discussion sessions, participants were able to express the obstacles faced in financial management, so that the mentoring team could provide relevant solutions. In conclusion, financial literacy training and app technology support MSME financial management. The adoption of digital applications improves efficient record-keeping and strengthens financial risk management.